2008
DOI: 10.1016/j.asj.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Functional Capacity Outcomes Following Reduction Mammaplasty

Abstract: Reduction mammaplasty improved self-esteem and functional capacity and relieved pain in the lower back region in patients with breast hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 10 publications
3
51
0
2
Order By: Relevance
“…This pain in the neck region reported by this patient might be caused by another disease or condition other than the breast pathology. Sabino (2008) stated reduction mammaplasty relieved pain in the lower back region in patients with breast hypertrophy [18]. Relief from the pre-operative complications by patients in the current study is confirmed in a similar study by Davis et al (1995); they found out that reduction mammaplasty decreased breast size and significantly relieved pre-operative symptoms associated with mammary hypertrophy [19].…”
Section: Physiological Complicationssupporting
confidence: 79%
“…This pain in the neck region reported by this patient might be caused by another disease or condition other than the breast pathology. Sabino (2008) stated reduction mammaplasty relieved pain in the lower back region in patients with breast hypertrophy [18]. Relief from the pre-operative complications by patients in the current study is confirmed in a similar study by Davis et al (1995); they found out that reduction mammaplasty decreased breast size and significantly relieved pre-operative symptoms associated with mammary hypertrophy [19].…”
Section: Physiological Complicationssupporting
confidence: 79%
“…Several randomised studies have proved the effects of breast reduction surgery (1)(2)(3)(4)(5)(6). Surprisingly the tient anxiety or depression (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction mammaplasty, surgical reduction of breast size, is the most effective means of improving symptoms and HRQOL in adults. 2,4,[6][7][8]13,14,[16][17][18][19][20][21][22][23][24][25] However, many parents and physicians are reluctant to consider surgical correction for adolescents. 26,27 Data on the impact of macromastia on younger patients are needed to better inform health care providers, patients, and families in making appropriate treatment decisions.…”
mentioning
confidence: 99%